1978
DOI: 10.1177/070674377802300809
|View full text |Cite
|
Sign up to set email alerts
|

Ecg Changes in Pure Imipramine Overdose as Function of Plasma Level*

Abstract: ECG changes occur with therapeutic doses of tricyclic antidepressants and cardiovascular conduction alteration is the lethal effect in overdoses on these drugs. These ECG changes depend on the plasma level and metabolism of the particular antidepressant. Information about the relative toxicity and metabolism characteristics can be obtained by studying overdoses if the attempt simply involves one tricyclic and no other drug ingestion. Such a case report involving a known quantity of imipramine is presented. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…35], at risk individ uals with a previous cardiovascular deficit [54,68] and interaction with other treatment regimens [29], Even the healthy are not to tally exempt from untoward effects, as clini cal and research reports have shown changes in cardiovascular status even within thera peutic dose range and plasma concentrations [10,36,56,69], Exercise and stress-related conditions may precipitate unexpected car diac effects [31], These factors illustrate the inherent difficulty for the clinician in the day-to-day use of antidepressant medication, but becomes more pronounced in overdose, accidently or otherwise, when it can lead to death due to cardiac asystole [6,8,23,70], Finally, to complicate matters further, one only has to look at the increased incidence of unexplained sudden death in the antidepres sant-treated group [24,52,72] to realise that we cannot, as yet, predict with any great cer tainty which individual will be prone to un wanted and unexpected cardiotoxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…35], at risk individ uals with a previous cardiovascular deficit [54,68] and interaction with other treatment regimens [29], Even the healthy are not to tally exempt from untoward effects, as clini cal and research reports have shown changes in cardiovascular status even within thera peutic dose range and plasma concentrations [10,36,56,69], Exercise and stress-related conditions may precipitate unexpected car diac effects [31], These factors illustrate the inherent difficulty for the clinician in the day-to-day use of antidepressant medication, but becomes more pronounced in overdose, accidently or otherwise, when it can lead to death due to cardiac asystole [6,8,23,70], Finally, to complicate matters further, one only has to look at the increased incidence of unexplained sudden death in the antidepres sant-treated group [24,52,72] to realise that we cannot, as yet, predict with any great cer tainty which individual will be prone to un wanted and unexpected cardiotoxic effects.…”
Section: Introductionmentioning
confidence: 99%